2017
DOI: 10.1101/cshperspect.a026757
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics ofC9orf72Expansions

Abstract: Repeat expansions in the promoter region of are the most common genetic cause of amyotrophic lateral sclerosis (ALS) and related disorders of the ALS/frontotemporal lobar degeneration (FTLD) spectrum. Remarkable clinical heterogeneity among patients with a repeat expansion has been observed, and genetic anticipation over different generations has been suggested. Genetic factors modifying the clinical phenotype have been proposed, including genetic variation in other known disease genes, the genomic context of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 147 publications
(210 reference statements)
0
14
1
Order By: Relevance
“…Furthermore, it is critical to note that protein abnormalities that define neurodegenerative diseases can be present before the onset of clinical features (Gibb and Lees 1988;Sparks et al 1994;Schmitt et al 2000;Adler et al 2010;Evidente et al 2011;Frigerio et al 2011;Milenkovic and Kovacs 2013;Dugger et al 2014c) and more than one neurodegenerative disease process can be found in an individual (Uchikado et al 2006a;Dugger et al 2014a). At present, diagnostic biomarkers are not available, except in rare cases in which a causative genetic mutation can be shown to cause the disorder (Ghasemi and Brown 2016;Gijselinck et al 2016;Hinz and Geschwind 2016;TCWand Goate 2016). Hence, specific in vivo biomarkers, including biofluid Amyloidoses Creutzfeldt -Jakob disease (genetic, variant, sporadic, iatrogenic) and molecular imaging markers (some highlighted in Kolb and Andres 2016;Seeley 2016), are a major research priority.…”
mentioning
confidence: 99%
“…Furthermore, it is critical to note that protein abnormalities that define neurodegenerative diseases can be present before the onset of clinical features (Gibb and Lees 1988;Sparks et al 1994;Schmitt et al 2000;Adler et al 2010;Evidente et al 2011;Frigerio et al 2011;Milenkovic and Kovacs 2013;Dugger et al 2014c) and more than one neurodegenerative disease process can be found in an individual (Uchikado et al 2006a;Dugger et al 2014a). At present, diagnostic biomarkers are not available, except in rare cases in which a causative genetic mutation can be shown to cause the disorder (Ghasemi and Brown 2016;Gijselinck et al 2016;Hinz and Geschwind 2016;TCWand Goate 2016). Hence, specific in vivo biomarkers, including biofluid Amyloidoses Creutzfeldt -Jakob disease (genetic, variant, sporadic, iatrogenic) and molecular imaging markers (some highlighted in Kolb and Andres 2016;Seeley 2016), are a major research priority.…”
mentioning
confidence: 99%
“…The repeat expansion mutation in C9orf72 , located on chromosome 9, is a major causal factor in the pathogenesis of both FTLD and ALS, forming a disease spectrum (Gijselinck et al, 2016). The hexanucleotide repeat of G 4 C 2 is expanded in patients and is generally considered to be pathological when the expansion contains ≥ 2–24 repeat units (Renton et al, 2011; Gijselinck et al, 2012, 2018; Van Mossevelde et al, 2018). The exact mechanism of disease is unclear so far.…”
Section: Genetic Screening For Known Causal Genes For Ftdmentioning
confidence: 99%
“…Other neuropathological disorders markedly linked to nuclear transport alterations are FTD and ALS (Gijselinck, Cruts, & Broeckhoven, ). The repeat expansion of the hexanucleotide GGGGCC (G4C2) in a noncoding region of the C9orf72 gene is the most common cause of sporadic and familial form of these disorders, but the molecular mechanisms of neurodegeneration are quite unknown.…”
Section: Protein Aggregates Affect Nucleocytoplasmic Transport Duringmentioning
confidence: 99%